186k views
3 votes
4n+ 6 -2n = 2(n + 3)
Please help me solve

User Gusto
by
4.7k points

2 Answers

6 votes

Answer:

Equation is true no matter what number you plug in for n.

Explanation:

4n + 6 -2n = 2(n + 3)

First we can divide the equation by 2 on both sides.

2n + 3 - n = n + 3

n + 3 = n + 3

n = n

Since n = n, this equation is always true no matter what number you plug in for n.

User Bagonyi
by
4.4k points
6 votes

Answer is provided in the image attached.

4n+ 6 -2n = 2(n + 3) Please help me solve-example-1
User Chestozo
by
5.1k points